Hydroxyapatite coated polymer microspheres for drug delivery - Zhang, Zhe (2012)
Hydroxyapatite (HA) can bond with protein via ion interaction and it is dissolvable in body fluid therefore it is of great interest to use as possible drug carrier for controlled release. Processing of HA-coated microspheres to incorporate protein (as drug) has been studied. However, long soaking time, poor drug coverage of the spheres and high pH conditions hinder practical applications. In this project, a new two-step process is used to prepare HA on polymer microspheres. As step 1, the polymer microspheres are soaked into calcium ion solution for 2 hours, then as step 2, phosphate ions are added to the solution. The concentration of supersaturated solution and soaking time of the microspheres are studied as two essential factors for the HA growth. 1.25mM calcium ion and 0.75mM phosphate ion are identified as the preferred concentration for HA growth on poly(lactic-co-glycolic acid) microspheres. In this process, HA is formed in the first hour of incubation as compared to several days in other processes. A full coverage of plate-like structured HA coating with sharp edge is achieved after only 24 hours. Two approaches of incorporation of drug into the HA coating are tested. One is to soak the HA-coated microspheres into a drug-containing solution (thus “drug-soaked HA”) and the other is to add the drug into the HA-forming solution and let the drug co-deposit on the microsphere at the time of HA formation (thus “drug-co-deposited HA”). As a model drug, bovine serum albumin is used in the test. For “drug-soaked HA”, HA-coated microspheres are soaked in 100, 500 and 1000μg/ml protein solution for 12 hours. For “drug-co-deposited HA”, 10, 100, 500 and 1000μg/ml protein solutions are mixed respectively into 0.75mM phosphate ion solution and then poured into the calcium solution containing the polymer microspheres and stirred for 24 hours. It is found that the protein in the supersaturated solution can strongly inhibit the nucleation and growth of HA formation. At 1000μg/ml, there is no formation of HA. At 10μg/ml, very little organic linked structure is observed. At 100 and 500μg/ml, clear net-linked structure of HA suggests protein is incorporated in crystal lattice of HA coating.